2003
DOI: 10.1073/pnas.0231020100
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the large FK506-binding protein FKBP51, an Hsp90-binding protein and a component of steroid receptor complexes

Abstract: The ability to bind immunosuppressive drugs such as cyclosporin and FK506 defines the immunophilin family of proteins, and the FK506-binding proteins form the FKBP subfamily of immunophilins. Some FKBPs, notably FKBP12 (the 12-kDa FK506-binding protein), have defined roles in regulating ion channels or cell signaling, and well established structures. Other FKBPs, especially the larger ones, participate in important biological processes, but their exact roles and the structural bases for these roles are poorly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
221
0
3

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 226 publications
(234 citation statements)
references
References 48 publications
3
221
0
3
Order By: Relevance
“…11,27 Herein, we showed a novel role for FKBP51 as a marker of melanocyte malignancy and involvement in the protection of melanoma against Rx-induced apoptosis. FKBP51 is a large immunophilin that exerts important biological functions in the cell, among which is the regulation of the steroid hormone response as a component of the steroid hormone receptor complex 28 and the control of NF-kB activation as a cofactor of the IKKa subunit in the IKK complex. 29 Our data showed that FKBP51 has a relevant role in counteracting apoptotic processes stimulated by Rx.…”
Section: Discussionmentioning
confidence: 99%
“…11,27 Herein, we showed a novel role for FKBP51 as a marker of melanocyte malignancy and involvement in the protection of melanoma against Rx-induced apoptosis. FKBP51 is a large immunophilin that exerts important biological functions in the cell, among which is the regulation of the steroid hormone response as a component of the steroid hormone receptor complex 28 and the control of NF-kB activation as a cofactor of the IKKa subunit in the IKK complex. 29 Our data showed that FKBP51 has a relevant role in counteracting apoptotic processes stimulated by Rx.…”
Section: Discussionmentioning
confidence: 99%
“…As shown (Fig. 2), in all four models the three domains of the structure are clearly discernible: the FKBP domain (with five antiparallel β-strands around a central α-helix, the so-called FK fold) (Sinars et al 2003), the three-TPR linker (i.e., helix-turn-helix × 3; abbreviated as 3TPR), followed by the CYN domain. While each domain structure is largely constant as expected, it is instructive that they show various degrees of orientation relative to each other, clearly due to both rotational and torsional flexibility of the 3TPR linker (Fig.…”
Section: Predicted Tertiary Structure Of a Dfimentioning
confidence: 99%
“…K422 is located in this C-terminal tail region, which has not yet been crystallized. 4 It is likely that the modification of K422 by SUMO might modulate the conformation of this region for FKBP51-Hsp90 interaction. Interestingly, in silico analysis reveals that Hsp90 bears SUMO-interacting motifs, which can mediate non-covalent SUMO binding and cooperate in interactions between binding partners and SUMOylated proteins.…”
Section: Discussionmentioning
confidence: 99%
“…The following plasmids used in this work were previously described, as indicated: FLAG-FKBP51 and FLAG-FKBP52; 5 GSTUbc9; 47 HA-GR and the GR reporter plasmid pΔ(TAT) 4 -Luc (TAT4-luc); 18 the NF-κB reporter plasmid (κB-luc); 48 and FLAG-Hsp90 and the Gaussia luciferase reporter plasmid. 32 The pHC-RED1-C1 plasmid was obtained from Clontech (Mountain View, CA, USA).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation